2017
DOI: 10.1159/000475926
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Amniotic Fluid along Gestation to the Prediction of Perinatal Mortality in Women with Early Preterm Premature Rupture of Membranes

Abstract: Introduction: To evaluate the largest vertical pocket (LVP) of amniotic fluid as a time-dependent factor to predict perinatal mortality in women with early preterm premature rupture of membranes (EPPROM). Material and Methods: Observational cohort studyof singleton pregnancies with EPPROM <24 weeks. Termination of pregnancy (TOP) was considered if the LVP was <2 cm at 7 days. The maternal and neonatal characteristics of ongoing pregnancies were recorded. Prediction of perinatal mortality was estimated based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Preterm prelabor rupture of membranes (PROM) is widely used as an inclusion criterion for predictions of other conditions. [1][2][3][4][5][6][7][8] The disease precedes 40%~50% of all preterm deliveries and arises from multiple disease pathways. 9 Yet, the antecedent remains unclear, and prognostic predictions lack proper sample sizes and external validation.…”
Section: Introductionmentioning
confidence: 99%
“…Preterm prelabor rupture of membranes (PROM) is widely used as an inclusion criterion for predictions of other conditions. [1][2][3][4][5][6][7][8] The disease precedes 40%~50% of all preterm deliveries and arises from multiple disease pathways. 9 Yet, the antecedent remains unclear, and prognostic predictions lack proper sample sizes and external validation.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Cobo et al evaluated the effects of single vertical pocket measurement, gestational age, maternal age, and previous invasive procedures on neonatal outcome in early PPROM patients. They observed that only the second week from membrane rupture was related to adverse neonatal outcome 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Presence of one of the following criteria was accepted as an adverse neonatal outcome: 1) APGAR score< 7 in 5 minutes, 2) pH of blood sampled from umbilical artery < 7.0, 3) need for intubation in the first 24 hours after delivery, 4) meconium aspiration, 5) presence of hypoglycemia, hyperbilirubinemia, hypothermia, intraventricular hemorrhage, necrotizing enterocolitis, seizures, sepsis, respiratory distress syndrome, and neonatal death in the first 28 days postpartum 16 .…”
Section: Methodsmentioning
confidence: 99%